Prescription and Prescriber Specialty Characteristics of Initial Opioid Prescriptions Associated with Chronic Use. Issue 12 (23rd October 2020) - Weiner, Scott G; Chou, Shih-Chuan; Chang, Cindy Y; Garner, Chad; El Ibrahimi, Sanae; Hallvik, Sara; Hendricks, Michelle; Baker, Olesya
Abstract: Objective: This study evaluated the characteristics of opioid prescriptions, including prescriber specialty, given to opioid-naïve patients and their association with chronic use. Design: Cross-sectional analysis of the Ohio prescription drug monitoring program from January 2010 to November 2017. Setting: Ohio, USA. Subjects: Patients who had no opioid prescriptions from 2010 to 2012 and a first-time prescription from January 2013 to November 2016. Methods: Chronic use was defined as at least six opioid prescriptions in one year and either one or more years between the first and last prescription or an average of ≤30 days not covered by an opioid during that year. Results: A total of 4, 252, 809 opioid-naïve patients received their first opioid prescription between 2013 and 2016; 364, 947 (8.6%) met the definition for chronic use. Those who developed chronic use were older (51.7 vs 45.6 years) and more likely to be female (53.6% vs 52.8%), and their first prescription had higher pill quantities (44.9 vs 30.2), higher morphine milligram equivalents (MME; 355.3 vs 200.0), and was more likely to be an extended-release formulation (2.9% vs 0.7%, all P < 0.001). When compared with internal medicine, the adjusted odds of chronic use were highest with anesthesiology (odds ratio [OR] = 1.46) and neurology (OR = 1.43) and lowest with ophthalmology (OR = 0.33) and gynecology (OR = 0.37). Conclusions: Eight point six percent of opioid-naïve individuals who received an opioid prescription developed chronic use. This rate varied depending on the specialty of the provider who wrote the prescription. The risk of chronic use increased with higher MME content of the initial prescription and use of extended-release opioids.